THE CORRELATION BETWEEN: AWARENESS OF HISTORY, RELIGIOUS VALUES AND MULTIETHNIC UNDERSTANDING WITH TOLERANCE ATTITUDE - Nurasiah, Nurasiah; Azis, Abdul; Munira, Widia (Paramita: Historical Studies Journal, 2019)
This research used descriptive method Correlation Ex Post Facto (CEPF). Participants in this research were 177 students from SMA Negeri department Banda Aceh. The author found the main problem of intolerance that is the low social behavior, attitudes individualistic, until the crisis of harmonization within individualistic students. Based on these problems, the authors designed a strategy in tackling the crisis of intolerance on students through the stages of correlation analysis Ex Post Facto (CEPF). The phases include test partial correlation analysis, simple regression and multiple regression. The results showed that: (1) there is a significant positive relationship between the sense of history with an attitude tolerance of students; (2) there is a significant positive relationship between religious values with tolerance of high school students Ã‚Â ; (3) there is a significant positive relationship between the understanding of multi-ethnic tolerance students; and (4) are jointly relationship between awareness of history, religious values and understanding of multi-ethnic tolerance with students. Based on the results of the study, authors state that the increased tolerance due to the high contribution of awareness of history, religious values and understanding of the multi-ethnic students through socialization in the process of teaching history.Keywords: Awareness of History, Religious Values, Multi-Ethnic Understanding, Tolerance Attitude Students.Ã‚Â Penelitian ini menggunakan metode deskriptif Correlation Ex Post Facto (CEPF). Partisipan dalam penelitian ini berjumlah 177 siswa dari depertement SMA Negeri Banda Aceh. Penulis menemukan masalah utama intoleransi yaitu rendahnya prilaku sosial, sikap individualistik, hingga krisis harmonisasi dalam diri individualistik siswa. Berdasarkan masalah tersebut penulis merancang strategi dalam menanggulangi krisis sikap intoleransi pada diri siswa melalui tahapan analisis korelasi Ex Post Facto (CEPF), dengan tahapan meliputi uji analisis korelasi parsial, regresi sederhana dan regresi ganda. Penulis menyajikan hasil penelitian menunjukan bahwa: (1) terdapat hubungan positif yang signifikan antara kesadaran sejarah dengan sikap Toleransi siswa SMA N Banda Aceh; (2) terdapat hubungan positif yang signifikan antara religious values dengan sikap toleransi siswa SMA N Banda Aceh; (3) terdapat hubungan positif yang signifikan antara pemahaman multi-etnis dengan sikap toleransi siswa SMA N Banda Aceh; dan (4) terdapat hubungan secara bersama antara kesadaran sejarah, religious values dan pemahaman multi-etnis dengan sikap toleransi siswa. Berdasarkan hasil penelitian penulis menyatakan bahwa, peningkatan sikap toleransi disebabkan oleh tingginya sumbangan kesadaran sejarah, religious values dan pemahaman multi-etnis siswa melalui sosialisasi dalam proses pembelajaran sejarah.Kata Kunci: Kesadaran Sejarah, Religious Values, Pemahaman Multi-Etnis, Sikap Toleransi Siswa.Ã‚Â